SARS-CoV-2 induces “cytokine storm” hyperinflammatory responses in RA patients through pyroptosis - Zheng, Qingcong; Lin, Rongjie; Chen, Yuchao; Lv, Qi; Zhang, Jin; Zhai, Jingbo; Xu, Weihong; Wang, Wanming (Frontiers in Immunology, 2022)
Background: COVID-19 is a pandemic disease that threatens the worldwide security of public health, and RA is the most common autoimmune disease. This study aims to investigate the biomarkers between COVID-19 and RA from the mechanism of pyroptosis and find effective disease-targeting drugs. Methods: We obtained the common gene shared by COVID-19, RA (GSE55235), and pyroptosis using bioinformatics analysis. The Co-genes were evaluated by GO, KEGG, and ClueGO for functional enrichment, the PPI network was built by STRING, and the k-means machine learning algorithm was employed for cluster analysis. Modular analysis utilizing Cytoscape to identify hub genes, functional enrichment analysis with Metascape and GeneMANIA, and NetworkAnalyst for gene-drug prediction. Network pharmacology analysis was performed to identify target drug-related genes intersecting with COVID-19, RA, and pyroptosis to acquire Co-hub genes and construct TF-hub genes and miRNA-hub genes networks by NetworkAnalyst. The Co-hub genes were validated using GSE55457 and GSE93272 to acquire the Key gene, and their efficacy was assessed using ROC curves; SPEED2 was then used to determine the upstream pathway. Immune cell infiltration was analyzed using CIBERSORT and validated by the HPA database. Molecular docking, molecular dynamics simulation, and MM-GBSA are used to explore and validate drug-gene relationships through computer-aided drug design. Results: COVID-19, RA, and pyroptosis-related genes were enriched in pyroptosis and pro-inflammatory pathways(NLRP3 inflammasome complex, death-inducing signaling complex, regulation of interleukin production), natural immune pathways (Network map of SARS-CoV-2 signaling pathway, activation of NLRP3 inflammasome by SARS-CoV-2) and COVID-19-and RA-related cytokine storm pathways (IL, NF-κB, TNF signaling pathway and regulation of cytokine-mediated signaling). Of these, CASP1 is the most involved pathway and is closely related to minocycline. YY1, hsa-mir-429, and hsa-mir-34a-5p play an important role in the expression of CASP1. Monocytes are high-caspase-1-expressing sentinel cells. Minocycline can generate a highly stable state for biochemical activity by docking closely with the active region of caspase-1. Conclusions: Caspase-1 is a biomarker of the exaggerated inflammatory response induced by SARS-CoV-2 via pyroptosis in RA patients. Minocycline can act against cytokine storm inflammation and against pyroptosis in patients with COVID-19 combined with RA by inhibiting the expression of caspase-1.